GIS-Based Virtual Field Trip as a Tool for Remote Education - Niki Evelpidou; Anna Karkani; Komi, Apostolia; Giannikopoulou, Aikaterini; Maria Tzouxanioti; Giannis Saitis; Spyrou, Evangelos; Gatou, Maria-Anna (Geosciences, 2022)
Geoscience courses, such as geology and geomorphology, require not only classroom lessons and laboratory exercises, but field trips as well. However, the COVID-19 restrictions did not allow the execution of most planned field trips, and an alternative needed to be developed. The use of virtual field trips is one such alternative. Through this research, we evaluate the usefulness of virtual field trips as tools for preparatory activities before an actual field trip takes place in the same area, and their contribution in providing a better understanding of geomorphological processes and landscape evolution. We performed a virtual navigation on the island of Naxos, Cyclades (Aegean Sea, Greece) for a series of virtual field trips, which took place during webinars in the framework of Erasmus+ CIVIS. The virtual field trip was also presented to the third-year students of the Faculty of Geology and Geoenvironment, National and Kapodistrian University of Athens, in the framework of the obligatory course of Geomorphology. Upon completion, all participating students were asked to fill in a questionnaire in order to evaluate the contribution of virtual field trips to their education regarding geomorphology and state their opinion as to whether they can supplement and/or substitute actual field trips. According to the results, virtual field trips can aid, but not substitute, the actual field trip. Most students mentioned that they would attend another virtual field trip in the future, both as an alternative to classroom lessons and as a means of preparation for an actual field trip, but not in order replace the actual one. Virtual field trips can significantly support the realization of actual ones, by introducing the necessary tectonic, geological and geomorphological background of a particular study area and offering more time for practical activities or field methodologies during the actual field trip.